The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1186/1471-2334-10-32
|View full text |Cite
|
Sign up to set email alerts
|

An optimal control theory approach to non-pharmaceutical interventions

Abstract: BackgroundNon-pharmaceutical interventions (NPI) are the first line of defense against pandemic influenza. These interventions dampen virus spread by reducing contact between infected and susceptible persons. Because they curtail essential societal activities, they must be applied judiciously. Optimal control theory is an approach for modeling and balancing competing objectives such as epidemic spread and NPI cost.MethodsWe apply optimal control on an epidemiologic compartmental model to develop triggers for N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 41 publications
(56 reference statements)
0
77
0
Order By: Relevance
“…in agreement with the fitting procedure obtained from the lower bounds of the uncertain initial data. In Figure 7 we represent the evolution of the expected value of the number of infected obtained by the controlled model in the presence of initial random data (29) and uncertain contact frequency (30). The value µ = 10 have been chosen accordingly to the WHO suggestions that around 80% are asymptomatic 1 .…”
Section: Test 2: Impact Of Uncertain Data On the Epidemic Outbreakmentioning
confidence: 99%
See 1 more Smart Citation
“…in agreement with the fitting procedure obtained from the lower bounds of the uncertain initial data. In Figure 7 we represent the evolution of the expected value of the number of infected obtained by the controlled model in the presence of initial random data (29) and uncertain contact frequency (30). The value µ = 10 have been chosen accordingly to the WHO suggestions that around 80% are asymptomatic 1 .…”
Section: Test 2: Impact Of Uncertain Data On the Epidemic Outbreakmentioning
confidence: 99%
“…Test 2. Evolution of expected number of infected and their confidence bands for the calibrated control model with ψ(I) = I q /q, q = 1, 2 with uncertain initial data(29) with µ = 10 and uncertain reproduction number (30) with α = 1 in the case of COVID-19 outbreak in Italy.…”
mentioning
confidence: 99%
“…Novel insights on the optimal allocation of economic resources were also obtained from approaches embedding compartmental models into optimization frameworks such as optimal control theory or dynamic programming [39,45,[68][69][70][71]. For instance Lee et al [40], using optimal control theory, identified the optimal way to dynamically allocate control measures such as antiviral allocation and isolation, subject to the dynamics of the pandemic and the effects of the control measures on those dynamics.…”
Section: Economic Aspectsmentioning
confidence: 99%
“…The natural framework to study epidemic problems is the optimal control, aiming at determining the best action with respect to conflicting requirements, such as using as less resources as possible while maximising the effects, that is minimizing the number of infected patients, Refs. [15,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%